(untitled) (Global Journal of Medical Research, 2022)
Human papillomavirus HPV infection is the most common sexually transmitted disease globally affecting mainly women and being responsible for developing oral and cervical cancer This study aims to determine the presence of HPV and its high and low- risk subtypes in women who submitted to the HPV genotyping test